2016
DOI: 10.5152/balkanmedj.2016.151385
|View full text |Cite
|
Sign up to set email alerts
|

Health and Roma People in Turkey

Abstract: Background:The research and published literature on Roma health in Turkey is much more limited than in other European countries. Among these, there are hardly any published literature focusing on the health status, health indicators and health behaviors. Aims: The aim of this research is to describe the perceptions of health-related concepts and access and the use of health services and social determinants of the health of Roma people in Turkey. Study Design: Descriptive qualitative survey. Methods: The partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 17 publications
1
8
0
2
Order By: Relevance
“…These authors list five key predictors of culture-related communication problems: cultural differences in explanatory models of health and illness; differences in cultural values; cultural differences in patients’ preferences for doctor-patient relationships; racist/perceptual biases; and linguistic barriers [ 11 ] (p. 21). All of these findings concerning ethnic minorities in general have also been observed in studies focused specifically on the Roma [ 12 , 13 , 14 , 15 , 16 ]. However, differences should also be recognised, especially in the current context of anti-Gypsyism [ 17 ], a racism that is also operating in healthcare settings.…”
Section: Introductionsupporting
confidence: 61%
See 1 more Smart Citation
“…These authors list five key predictors of culture-related communication problems: cultural differences in explanatory models of health and illness; differences in cultural values; cultural differences in patients’ preferences for doctor-patient relationships; racist/perceptual biases; and linguistic barriers [ 11 ] (p. 21). All of these findings concerning ethnic minorities in general have also been observed in studies focused specifically on the Roma [ 12 , 13 , 14 , 15 , 16 ]. However, differences should also be recognised, especially in the current context of anti-Gypsyism [ 17 ], a racism that is also operating in healthcare settings.…”
Section: Introductionsupporting
confidence: 61%
“…All in all, the lack of cultural sensitivity in healthcare systems is often fed by the intolerance, prejudices, and stereotypes of some healthcare personnel towards all non-white clients, accentuated in the case of the Roma people as a result of long-lasting discrimination [ 14 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ]. Although some efforts have been dedicated to exploring the barriers that the Roma community face in accessing the healthcare system in Spain [ 32 ], more research specifically addressing how these barriers are embodied, and looking at the cases not only of those who are in the most vulnerable social positions, but also of those who have stable socioeconomic positions and higher cultural capitals, can help us to better understand how anti-Roma sentiments underlie society, and specifically, the health-care system.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the compulsory health insurance system in the RS and the constitutionally guaranteed rights to health, there are other social determinants, such as poverty and education that override Roma women's capacity to address their health needs. Ekmekçi found a link between financial constraints and poorer socioeconomic determinants that leads to a high level of unmet health needs (20). Economic barriers include formal and informal payment of charges for health services, lack of financial resources for transport to the health care institutions, inability to pay communication costs, and limited funds for prescriptions or to pay health insurance costs (21).…”
Section: Discussionmentioning
confidence: 99%
“…A survey conducted between 1986 and 1989 in low income areas of Istanbul showed that women think that abortion is ethically permissible (Gürsoy 1992). Another field survey conducted in five different provinces of Turkey in 2014 showed that women widely have abortion and that they do not consider it a sin or an unethical behavior, since giving birth to a child whom they are incapable of looking after, would be a greater sin (Ekmekci 2015, 2016). The participants’ approval for abortion was higher in cases, when the pregnant is single, thinks she has way too much children than she can take care of or if the mother has disabled children.…”
Section: Abortion In Turkeymentioning
confidence: 99%